2013
DOI: 10.1021/jp407120j
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanisms of ZnO Nanowires: The Crucial Role of Crystal Orientation and Polarity

Abstract: International audienceZnO nanowires grown in liquid phase are considered as promising building blocks for a wide variety of optical and electrical devices. However, their structural morphology is still limited by the lack of understanding of their growth mechanisms. We have systematically investigated the effects of orientation and polarity of ZnO monocrystals acting as substrates on the formation mechanisms of ZnO by chemical bath deposition. Under identical growth conditions, two-dimensional layers develop o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 62 publications
2
74
0
Order By: Relevance
“…The structural properties of ZnO NWs strongly depend on the structural morphology of the ZnO seed layer, such as nanoparticle size, density, orientation, polarity, and porosity. 12,13 The growth conditions in the chemical bath such as the nature of chemical precursors and related concentrations, pH, and additives are also crucial for controlling the structural morphology of ZnO NWs. 7−11 Owing to the expected increase in light harvesting 14 and extraction efficiency, as well as charge carrier management, the integration of ZnO NWs has recently been achieved in optoelectronic and photovoltaic devices such as light emitting diodes 15 and nanostructured solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The structural properties of ZnO NWs strongly depend on the structural morphology of the ZnO seed layer, such as nanoparticle size, density, orientation, polarity, and porosity. 12,13 The growth conditions in the chemical bath such as the nature of chemical precursors and related concentrations, pH, and additives are also crucial for controlling the structural morphology of ZnO NWs. 7−11 Owing to the expected increase in light harvesting 14 and extraction efficiency, as well as charge carrier management, the integration of ZnO NWs has recently been achieved in optoelectronic and photovoltaic devices such as light emitting diodes 15 and nanostructured solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…If a rough or seeded substrate is immersed in that solution, well ordered vertically oriented ZnO NRs can be grown on it [22][23][24]. The seed layer, which consists of zinc oxide crystallites preformed or spin-coated on the substrate,[25][26][27] promotes the heterogeneous nucleation on the substrate (while the homogenous one typically occurs in the bulk solution).…”
mentioning
confidence: 99%
“…We attribute the decreased nanorod length (270 nm) to an initially reduced [002] crystalline surface area in the seed layers annealed at 150 °C (table ) compared to nanorods grown on seed layers annealed at higher temperatures (310 nm at 250 °C and 410 nm at 350 °C). Nanorod growth along planes other than the [002] plane is unlikely due to lattice mismatch, and studies on the growth of ZnO nanorods on top of ZnO monocrystals as substrates demonstrated that nanorods grow only on surfaces which provide an exposed c‐plane . During nanorod deposition, the ZnO seed layer is exposed to depletion/etching and attachment simultaneously .…”
Section: Resultsmentioning
confidence: 99%